Structural Balance as an Indicator of the Assessment of Fiscal Policy in the Euro Area Countries - Giżyński, Juliusz (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The main aim of this article is to submit an idea of the structural balance within the euro area fiscal surveillance framework, characterising its main methodological aspects and analysing the level of structural balance in the euro area countries in the time of recovery from the financial crisis. Since the first reform of the Stability and Growth Pact, which took place in 2005, structural balance has played the key role as an indicator of fiscal surveillance in the euro area. This balance is cyclically adjusted net of one – off and temporary measures. It enables to estimate the level of fiscal consolidation measures, which are being introduced by the euro area countries, and recognise the results of the actions taken.